Comparative Study On The Properties Of Rice Straw/Polypropylene And Micaceous Clay/Polypropylene Composites - Nallis, Kry (2009)
Comparative study on the properties of an agricultural waste, rice straw (RS), reinforced polypropylene composites and mineral filler, micaceous clay (MC), reinforced polypropylene composites was investigated in this study. Suatu kajian perbandingan ke atas sifat suatu komposit polipropilena tetulang jerami (hasil buangan pertanian) dan tetulang lempung bermika (pengisi mineral) telah dilakukan.